Indole Acetic Acid Oxidase Activity in Brinjal as Influenced by Fertiliser Treatments - Rosamma Abraham (Department of Soil science and Agricultural chemistry, 1998)
'The present investigation was carried out in the College of Horticulture, Vellanikkara, during 1995-1997. The study was aimed to find out the effect of organic manu ring and chemical fertilisers on the levels of lAA and its influence on growth and yield of brinjal by monitoring the activity of indole acetic acid oxidase in plant leaves at different stages of plant growth. The experiment was laid out in randomised block design with 13 treatments and three replications. The treatments include combinations of different levels of organic manure and fertiliser, that is, zero, normal recommended dose and double recommended dose with an without foliar application of 150 ppm !AA and absolute control. IAA oxidase activity was found to increase with the age of the plant upto the tlowering stage and thereafter it was found to decrease. Application of treatment was found to influence the IAA oxidase activity only at the fruiting stage of the plant. Height, number of branches; flowers and fruits per plant and average fruit weight were not significantly influenced by the treatments. Howe~er fruit yield in brinjal was increased by the application of FYM, fertiliser and laa. Fruit yield was increased when IAA was applied along with FYM or fertiliser alone or in combination. Plant N content was found to decrease from vegetative to flowering phase and thereafter it was found to increase. But the application of different treatments could not enhance the plant N content significantly.